DETERMINANTS OF LOW BIRTH WEIGHT IN URBAN AREA OF INDONESIA: ANALYSIS OF THE 2017 INDONESIAN DEMOGRAPHIC AND HEALTH SURVEY - Fatqiatul Wulandari; Trias Mahmudiono; Mahmud Aditya Rifqi (Universitas Airlangga, 2022)
In developing countries, low birth weight (LBW) is still considered a major public health problem among infants. The national prevalence of LBW in Indonesia is quite high and ranked 6th for LBW cases among countries in Southeast Asia. This paper aimed to study the determinant of LBW especially in the urban area of Indonesia due to the wide availability of household survey data and the limited research of LBW with a large number of samples. This study used the latest data from the 2017 Indonesian Demographic and Health Survey (IDHS). A bivariate analysis using the Chi-square test and a multivariate analysis tested by logistic regression was done. As many as 7,321 women of childbearing age-aged 15-49 years from the urban areas were selected as the final sample. A number of 6.7% of infants were born with LBW with a mean birth weight of 3,677 grams. This study showed a significant relationship between birth interval and maternal complication and LBW (OR:0.74; OR:2.21). Women’s level of education also appeared to be significantly related to LBW (OR:0.82). The conclusion of the study was that birth interval, maternal complications, and mother’s education level were closely related to LBW. Therefore, collaboration between health services, health centers, government sectors, and academicians is needed to provide standard ANC services followed by routine maternal health education is expected to reduce LBW numbers in urban areas of Indonesia.